Spatializing the emerging geography of urban system in China: based on live streaming commerce - Zou, Lin; Guoqing, Lyu; Zhu, Yi-Wen; Yan, Simin; Xumin, Zhang (Cities, 2023)
Although live streaming commerce (LSC) has become a daily phenomenon in the digital economy, its spatial impact is still not yet fully understood. LSC is typical online-offline producer-customer intermediation type of the platform urbanism. Based on unique data from Huitun on the LSC activities in Taobao (Alibaba), we trace how digital streamers/platform with their own geographies connect suppliers with customers from different regions. Most digital streamers are located in urban areas, so they form a kind of urban intermediation among different regions. We argue that digital streamers, product suppliers, and customers form new urban systems because of their relational work and intermediation. We also show how intermediary cities emerge and change their positions in the new urban system. We demonstrate that retail is no longer based on the traditional service radius within a city but on a function of the intermediation of customers and suppliers from different regions. Finally, we provide evidence indicating that market access, transport infrastructure, and market consumption capacity are important factors that help explain such positions.
Online verfügbar: 16. Oktober 2023
Gesehen am 01.12.2023